Anti-Inflammatory Effect of Columbianetin on Lipopolysaccharide-Stimulated Human Peripheral Blood Mononuclear Cells. (5th April 2018) - Lu, Junying; Fang, Keyong; Wang, Shiji; Xiong, Lingxin; Zhang, Chao; Liu, Zhongmin; Guan, Xuewa; Zheng, Ruipeng; Wang, Guoqiang; Zheng, Jingtong; Wang, Fang
Abstract : Dysregulated inflammation is increasingly considered as the main cause of many diseases on which NOD1/NF- κ B pathway plays an important role. Columbianetin (CBT) is derived from the root of the Chinese herb Radix Angelicae Pubescentis for treating inflammatory diseases. Although the anti-inflammatory effect of CBT has been reported, its anti-inflammatory mechanism was poorly studied. In this study, we explored the anti-inflammatory pathway of CBT in lipopolysaccharide- (LPS-) stimulated human peripheral blood mononuclear cell (PBMC) model. Inflammatory cytokine production in culture supernatant was assessed using ELISA assay, and the possible anti-inflammatory pathway of CBT was screened using qPCR array and enrichment analysis with DAVID6.8. To further confirm the targeted pathway of CBT, we pretreated PBMC with the selective NOD1 inhibitor ML130 and then measured the protein levels of the pathway by Western blotting. The result showed that CBT effectively suppressed the expressions of TNF- α, IL-6, MCP-1, and IL-1 β in a dose-dependent manner and significantly downregulated 19 out of 32 differentially expressed genes, most of which were involved in the NOD1/NF- κ B pathway, and also showed that CBT remarkably inhibited LPS-induced NOD1, RIP2, and NF- κ B activation. Furthermore, the inhibitory effects of CBT on NOD1/NF- κ B pathways were blocked by ML130. These findings indicated that CBT inhibits the production of inflammatory cytokines induced by LPS involved in the downregulation of NOD1/NF- κ B pathways.